2012
DOI: 10.1515/revneuro-2012-0052
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of serotonin type 3 receptors in the successful extinction of cued or contextual fear conditioned responses: interactions with GABAergic signaling

Abstract: The changes in serotonin type 3 (5-HT) receptor activity influence memory and emotional regulation,the two essential components underlying the successful extinction of conditioned fear. These studies determined if blocking 5-HT3 receptors with granisetron influences the extinction of fear in male Sprague-Dawley rats. In Experiment 1, preextinction granisetron (0.5 or 1.0 mg/kg intraperitoneally) d~d not affect cued extinction learning but enhanced memory for the extinction session on retention test given 24 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
(68 reference statements)
0
17
1
Order By: Relevance
“…In contrast to our findings, Park and Williams (2012) reported that systemic injection of a 5-HT 3 receptor antagonist (granisetron) facilitated the memory of cued and contextual fear extinction in rats. However, there are several points of difference between our experiments and theirs, which could account for the differences between the results obtained.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our findings, Park and Williams (2012) reported that systemic injection of a 5-HT 3 receptor antagonist (granisetron) facilitated the memory of cued and contextual fear extinction in rats. However, there are several points of difference between our experiments and theirs, which could account for the differences between the results obtained.…”
contrasting
confidence: 99%
“…Second, the experimental paradigms differed. Park and Williams (2012) used passive avoidance paradigms to measure conditioned contextual fear, whereas we used the fear conditioning paradigms described above. These two behavioral tasks are known to be fear learning tests; however, the requirements vary across learning tasks.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, serotonin receptors have been implicated in playing a role in emotion-related behaviors in the hippocampus and the mPFC. Although all 5-HT receptors have been identified within the amygdala, particular attention has been paid to the 5-HT 1A and 5-HT 2C receptors (Park and Williams, 2012; Asan et al, 2013). Specifically, the 5-HT 1A receptors in the CE have been shown to be involved in the reduction of anxiety-like behaviors while 5-HT 2C receptors are associated with an increase in anxiety-like behaviors (Li et al, 2012).…”
Section: The Functional Subsets Of 5-ht Neurons Based On Functional Nmentioning
confidence: 99%